2013
DOI: 10.1063/1.4820565
|View full text |Cite
|
Sign up to set email alerts
|

Development of analytical vibration solutions for microstructured beam model to calibrate length scale coefficient in nonlocal Timoshenko beams

Abstract: The present study takes an analytical approach for solving the free vibration problem of a microstructured beam model, in which transverse displacement springs are added to allow for the transverse shear deformation effect in addition to the rotational springs. The exact vibration frequencies for the discrete microstructured beam model with simply supported ends are obtained via matrix decomposition. In addition, a general solution technique involving the use of Pad e approximants for the continualization proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 50 publications
3
31
0
Order By: Relevance
“…It has been recently shown that discrete elastic structural systems can be effectively modeled by an Eringen's type nonlocal elasticity law for bending, buckling or vibrations of microstructured beams [5][6][7][8][9]. The nonlocal results are valid not only for discrete axial systems, discrete bending systems, but also for shear/bending discrete systems [10,11]. In other words, Eringen's nonlocal elasticity [12] can be theoretically supported by some micromechanics or microstructural arguments, and the length scale of the nonlocal elastic model can be analytically calibrated with respect to the size of the microscopic repetitive cell.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recently shown that discrete elastic structural systems can be effectively modeled by an Eringen's type nonlocal elasticity law for bending, buckling or vibrations of microstructured beams [5][6][7][8][9]. The nonlocal results are valid not only for discrete axial systems, discrete bending systems, but also for shear/bending discrete systems [10,11]. In other words, Eringen's nonlocal elasticity [12] can be theoretically supported by some micromechanics or microstructural arguments, and the length scale of the nonlocal elastic model can be analytically calibrated with respect to the size of the microscopic repetitive cell.…”
Section: Introductionmentioning
confidence: 99%
“…The basic property of the nonlocal functions can be seen in Lim et al [52]. Some studies [66][67][68][69][70][71] have been presented to identify and incorporate the nonlocal parameter e 0 a for different small-scaled structures. It is worth mentioning that, different materials produce different values of the material characteristic parameter l, some studies [53,72,73] have studied the material characteristic parameter l for different materials.…”
Section: Nonlocal Strain Gradient Theorymentioning
confidence: 98%
“…Reddy [6] studied the nonlocal theories for bending, buckling and vibration of beams. Duan et al [7] used microstructured beam to calibrate length scale coefficient in nonlocal beams. Zhang et al [8] and Wang et al [9] proposed the calibration of Eringen's small length scale coefficient for initially stressed vibrating nonlocal Euler beams based on microstructured beam model.…”
Section: Introductionmentioning
confidence: 99%